257 Effect of Drinker Design on Growth and Water Disappearance of Nursery Pigs. (12th April 2022) - Vande Pol, Katherine D; Grohmann, Nicholas; Weber, Tom; Ritter, Matthew J; Ellis, Michael
Abstract: Changes in genetic potential and management practices may have altered the water requirements of nursery and other classes of pigs. However, there are few recent estimates of the water intake of nursery pigs or effects of factors such as drinker design on intake levels. The objective of this study was to evaluate the effect of two Drinker Design treatments (Nipple vs. Cup) on the water disappearance of nursery pigs (weaning to 6 wk post-weaning; 6.4 ± 1.07 to 22.0 ± 3.39 kg live body weight). A RCBD was used with a total of 336 pigs, housed in 16 pens of 21 pigs in 2 rooms (8 pens/room). Pens had fully slatted concrete floors; floor space was 0.32 m 2 /pig; there was 1 feeder and 1 drinker per pen. Pigs were fed corn-soybean based diets (meal form) formulated to meet or exceed nutrient requirements (NRC, 2012). Pigs and feeders were weighed at the start and end of the study. Water disappearance was measured using water-flow meters fitted to the pipeline supplying the drinker in each pen. Data were analyzed using the PROC MIXED procedure of SAS; models accounted for the fixed effect of Drinker Design and random effect of block. Drinker Design did not affect ( P > 0.05) growth performance (Table 1). However, average daily water disappearance was 19.1% greater ( P ≤ 0.05) for Nipple vs. Cup drinkers. Consequently, water:feed disappearance ratio was 15.8% greater ( P ≤ 0.05) for the Nipple than the Cup treatment. In conclusion, these results suggest that water disappearance from nipple drinkers was greater than for cup drinkers. The lack of an effect of Drinker Design on pig growth performance suggests that this treatment difference was most likely due to greater water wastage for nipple drinkers rather than any effect on water intake per se.